The problems of development of the Czech historic novel in 1940–60s - Vostrykаva Alena U. (Journal of the Belarusian State University. Philology, 2019)
The article highlights the problems of the development of the historical genre in the Czech literature of the 1940–60s, gives a broad panorama of the development of the historical prose of the period, authors and their works are named, their place and role in the literary process are determined, and their ideological and genre-style features are characterized. The problem of the traditional and innovative in the Czech historical novel of this time is being solved. The main trends of development within each time interval, connected with certain historical and cultural events in Czechoslovakia, are singled out.